A note on the Effect of Deep Ploughing on Basic Infiltration Rate of Soils, Root Growth and Grain Yields Under Rainfed Agriculture at Anantaput - Reddy, D Subbarami; Reddy, D Ramachandra; Chary, G Venkatanadha (Annals of Arid Zone, 2016)
.